Modelo de ocupación agropecuario sostenible en áreas rurales de la zona Andina (2022)
The reality of the rural sector in Colombia reflects a clear disparity between decent living conditions between the countryside and the cities, there are multiple causes of such inequality: violence, poverty, corruption, armed conflict, etc. We observe among so many adversities that the conditions of soil productivity are being wasted, only 7 million hectares with agricultural vocation of 22 million possible are used to produce food and the % of these 7 million hectares that are destined for livestock use exceeds 80 %, In this way it is necessary to establish different occupation parameters to guarantee conditions of sustainability and productivity that allow the agricultural producer to be more productive in less space to diversify the productive possibilities in the recovered area, recover and safeguard the destroyed ecosystems and establish better living conditions and bridge the gap between the cities and the countryside.